CP-116 Evaluation of the clinical significance and value of a clinical pharmacy service at a teaching hospital. (25th February 2017) - Mueller, D; Pichler, M; Kaiser, G; Brozek, W; Kirchdorfer, K; Zwettler, E; Weidmann, AE
Abstract : Background: Clinical pharmacy services (CPS) have been shown to provide significant clinical benefits for patient care. The paucity of literature reports within the Austrian healthcare system highlights the urgent need for studies providing evidence for CPS. Purpose: To assess the clinical significance and value of CPS by determining the number, type and clinical significance of identified drug related problems (DRPs), acceptance rate of suggested interventions and their benefit to inpatient care. Material and methods: This was a two phase mixed method study: (1) prospective descriptive study of number and type of identified DRPs, suggested interventions and their acceptance rate based on a validated classification system 1 ; (2) independent expert panel rating of the clinical significance of identified DRPs and the clinical value of suggested interventions based on a reliable rating method. 2 The setting was a 455 bed teaching hospital in Vienna. The CPS was across two surgical, two trauma, one cardiology and two internal medicine wards. Results: The pharmacists identified 200 DRPs in 162 patients giving an average of 1.2 (±1.8) DRPs/patient: the most common DRPs included 'drug interaction' (23%), 'drug without indication' (20%) and 'non-conformity to guidelines/contraindication' (14%). The most frequently suggested interventions were 'drug discontinuation' (32%), 'dose adjustment' (18%) and 'drug monitoring' (18%). 70% of the suggested interventions were accepted by the medical professionals. The experts assessed 84% of the DRPs as clinically significant (67%) or serious (17%), and 83% of the suggested interventions as significant (60%), very significant (22%) or extremely significant (1%). The overall inter-rater agreement was moderate for both the severity of error/event and the value of the pharmacy service (Kendall-W 0.525 and 0.461, respectively). Conclusion: The expert panel assessed the CPS as of great clinical significance and of high clinical value to inpatient care. The prevalence of identified DRPs and the high rate of accepted interventions reflect the contribution of the service to the reduction and prevention of adverse drug events, treatment failure and the achievement of therapy goals. This suggests that the CPS is a valuable contribution to improve patient safety and patient care. References and/or acknowledgements: 1. Allenet B, et al. Pharm World Sci2006;28:181–8. 2. Overhage JM, Lukes A. Am J Health Syst Pharm1999;56:2444–50. Many thanks to the expert panel members for their invaluable contribution. No conflict of interest